Tribological properties of metal matrix composite coatings produced by electrodeposition of copper. (May 2015) - Bhat, A.; Bourell, D.
<x content-type="archive" xml:space="preserve">Abstract</x> Porous templates of graphite and silicon carbide–carbon fibres were fabricated on a copper-110 alloy plate using indirect laser sintering. Copper was deposited electrochemically into the pore network to achieve metal matrix composite coatings using a redox flow battery apparatus. Densities of 89 and 96% were achieved on the copper–graphite composite and copper–SiC composites, respectively. The coefficient of friction and volumetric rate of material loss was determined under a load of 5 N for the coatings and three different sliding speeds of 1200, 1800 and 2400 mm min−1 in sliding wear test. The copper–SiC coatings exhibited a higher wear resistance compared to the copper-110 alloy, while the copper–graphite coatings exhibited a very low coefficient of friction.